Urbanização do processo escolar rural - Leite, Sérgio Celani (1996)
Historically, we realized that rural education in Brazil has always been on the margins of the school process, although agricultural production and rural people themselves were the focus of economic and political interests. Economical in terms of maximum exploitation of land and farm work; politicians, as an element to be directed at the ideological-cultural level, in order to allow the dominant classes to remain in power. Surviving from a cramped structure, the rural school outlined its trajectory through governmental disinterest in stipulating its own educational policy, leading it to an '' imitation '' of the urban process, without realizing that, by proceeding in this way, it competed for a mischaracterization of the process itself and, jointly, of peasant society. Under the influence of post-World War II urbanization and developmentalist guidelines, the contempt for formal schooling in the countryside and, consequently, the prioritization of informal education mechanisms, was accentuated.With the implementation of the Rural Extension (mechanism created by agreement between the governments of Brazil / USA), it was intended to modernize and immediately increase production / productivity in the countryside. Linked to the capitalist-liberal matrixes, these urbanizing mechanisms reinforced the ties of economic, social and political dependence of micro and small rural landowners, ultimately not allowing a satisfactory socio-cultural balance in the rural environment. On the contrary, it enabled the impoverishment of rural men and their geographical expulsion; it gave rise to the entry of business groups in the countryside, accentuating the levels of exploitation on peasant society; it inserted values ​​that were alien to the praxis of that society and, above all, minimized the fundamental principles of rural education (socio-cultural transmission of the behavioral components of that human group). In this way, the urbanization of the rural environment, in a comprehensive socio-historical analysis, allowed the proliferation of disconcerting and, at the same time alienating, ruptures in life, in the relations of work and production, in the socio-political and cultural / educational organization of peasant peoples. What is perceived in this case is an almost total usurpation of the rights of the peasant, as a citizen and subject of the world in which he lives. However, the rural school as a social value remains dialectically, between the 'traditional' and the new, between the 'praxis' and the urban-industrial massification, between the natural situations of the countryside and the demands of the urban environment, in an attempt to to find, or better to say, to rediscover its own identity. In this sense, the need arises for an educational policy aimed especially at rural society, based on the principles of human solidarity, citizenship and the rights of all to experience democracy, social justice and, above all, access to cognitive-intellectual means of human knowledge.